Integrated management of charcoal rot disease in susceptible genotypes of mungbean with soil application of micronutrient zinc and green manure (prickly sesban) - Shoaib, Amna; Khan, Kashif Ali; Awan, Zoia Arshad; Jan, Basit Latief; Kaushik, Prashant (Frontiers in Microbiology, 2022)
Charcoal rot disease is incited by the soil-borne fungus Macrophomina phaseolina (Tassi). Goid is a challenging disease due to long-term persistence of fungus sclerotia in the soil. This study assessed the potential of zinc (Zn: 1.25, 2.44, and 5 mg/kg) and green manure (GM: 1 and 2%) in solitary and bilateral combinations to alleviate infection stress incited by M. phaseolina on disease, growth, physiology, and yield attributes in mungbean. A completely randomized design experiment was conducted in potted soil, artificially inoculated with the pathogen, and sown with surface-sterilized seeds of mungbean genotypes (susceptible: MNUYT-107 and highly susceptible: MNUYT-105). Concealment of plant resistance by M. phaseolina in both genotypes resulted in 53–55% disease incidence and 40–50% plant mortality, which contributed in causing a significant reduction of 30–90% in attributes of growth, biomass, yield, photosynthetic pigment, and total protein content with an imbalance of production of antioxidant enzymes (polyphenol oxidase, superoxide dismutase, catalase, and peroxidase). Soil application with Zn-based fertilizer (ZnSO4: 33%) in combination with GM significantly managed up to 80% of the charcoal rot disease, hence improving growth (50–100%) and physiochemical (30–100%) attributes and sustainably enhancing grain average yield (300–600%), biological yield (100–200%), and harvest index (100–200%) in mungbean plants. The heat map and principal component analyses based on 19 measured attributes with 16 treatments separated Zn (2.44 or 5 mg/kg) combined with 2% GM as the best treatments for alleviating charcoal rot disease stress by improving growth, yield, and biological attributes to an extent to profitable farming in terms of harvest index (HI) and benefit-cost ratio (BCR).